Measurement properties of gait speed tests in community-dwelling older adults - Mehdipour, Ava (My University, 2024)
Gait speed tests are one of the most commonly used measures of mobility for community- dwelling older adults. However, their measurement properties should be carefully examined before clinical decisions are made from scores. The aim of this doctoral dissertation was to evaluate the measurement properties of gait speed tests in community-dwelling older adults. The following studies were conducted to address this aim: 1) a systematic review to summarize the measurement properties of usual and fast gait speed tests in community-dwelling older adults, 2) a secondary data analysis examining the validity and responsiveness of a gait speed test in a large, Canadian sample of community-dwelling older adults, and 3) a prospective cohort study evaluating the measurement properties of virtually administered gait speed tests in community-dwelling older adults. Findings demonstrated evidence for the reliability of gait speed tests when administered under different protocols (e.g., in-person and virtually, and usual and fast pace), their construct validity with respect to evaluating locomotor capacity, and their responsiveness in relation to measures of locomotor capacity when performed at usual pace. Findings also highlighted the need for further testing of gait speed tests with higher quality studies. In conclusion, given the current evidence, gait speed tests can be used to monitor and compare community-dwelling older adults’ mobility.